Low carbohydrate diet and all cause and cause-specific mortality. Issue 4 (April 2021) - Akter, Shamima; Mizoue, Tetsuya; Nanri, Akiko; Goto, Atsushi; Noda, Mitsuhiko; Sawada, Norie; Yamaji, Taiki; Iwasaki, Motoki; Inoue, Manami; Tsugane, Shoichiro; ,; Tsugane, S.; et al.
Summary: Background: Evidence is limited regarding the association between low-carbohydrate diet (LCD) score and mortality among Asians, a population that consumes a large amount of carbohydrates. Objective: The present study examined the association between low-carbohydrate diet (LCD) score (based on percentage of energy as carbohydrate, fat, and protein) and the risk of total and cause-specific mortality among Asians. Design: This study was a prospective cohort study in Japan with follow-up for a median of 16.9 years involving 43008 men and 50646 women aged 45–75 years. Association of LCD score, LCD score based on animal sources of protein and fat, and LCD score based on plant sources of protein and fat with risk of mortality was assessed using Cox proportional hazards model. Results: A U-shaped association was observed between LCD score and total mortality: the multivariable-adjusted hazard ratios (HRs) (95% CI) of total mortality for lowest through highest scores were 1.00, 0.95 (0.91, 1.01), 0.93 (0.88, 0.98), 0.93 (0.88, 0.98), and 1.01 (0.95, 1.07) (P-non-linearity <0.01). A similar association was found for mortality from cardiovascular disease (CVD) and heart disease. LCD score based on carbohydrate, animal protein, and animal fat also showed a U-shaped association for total mortality (P-non-linearity <0.01). In contrast, LCD score based on carbohydrate, plant protein, and plant fat was linearly associated with lower total (HR, 0.89; 95% CI: 0.83, 0.94 for highest versus lowest quintile), CVD [0.82 (0.73, 0.92)], heart disease [0.83 (0.71, 0.98)], and cerebrovascular disease [0.75 (0.62, 0.91) mortality. Conclusions: Both LCD with high animal protein and fat and high-carbohydrate diet with low animal protein and fat were associated with higher risk of mortality. Meanwhile, LCD high in plant-based sources of protein and fat was associated with a lower risk of total and CVD mortality.